1996
DOI: 10.1111/1523-1747.ep12329856
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Separate Control Mechanisms at the Message, Protein, and Enzyme Activation Levels for Transglutaminase During Calcium-Induced Differentiation of Normal and Transformed Human Keratinocytes

Abstract: We analyzed the effects of three different calcium concentrations on the RNA and functional protein levels of transglutaminase (TGase) and involucrin (INV) over time in culture. We compared the results in normal human keratinocytes with those in a squamous cell carcinoma, SCC4. The highest calcium concentration (1.2 mM) induced the greatest levels of INV and TGase message, INV protein, and rates of CE formation, but not maximal levels of TGase protein. By examining cytosol and membrane fractions of keratinocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 25 publications
3
58
0
Order By: Relevance
“…Interestingly, Gibson et al observed a distinction between welldifferentiated keratinocytes and poorly differentiated SCC4 cells with respect to calcium ion-induced involucrin expression. In particular, high calcium concentration induced involucrin mRNA and protein in keratinocytes but not in poorly differentiated SCC4 cells (Gibson et al, 1996). This similarity between calcium and hypoxia regulation might be important for understanding how hypoxia induces involucrin.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Interestingly, Gibson et al observed a distinction between welldifferentiated keratinocytes and poorly differentiated SCC4 cells with respect to calcium ion-induced involucrin expression. In particular, high calcium concentration induced involucrin mRNA and protein in keratinocytes but not in poorly differentiated SCC4 cells (Gibson et al, 1996). This similarity between calcium and hypoxia regulation might be important for understanding how hypoxia induces involucrin.…”
Section: Discussionmentioning
confidence: 85%
“…Induction occurs over a period of 2 h and is, therefore, relatively rapid. In contrast to SCC9 cells, hypoxia induces little or no involucrin in poorly differentiated SCC4 cells in spite of the fact that the involucrin gene is reported to be functional with ample quantities of involucrin mRNA present in these cells (Gibson et al, 1996). Interestingly, Gibson et al observed a distinction between welldifferentiated keratinocytes and poorly differentiated SCC4 cells with respect to calcium ion-induced involucrin expression.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperkeratinization is most pronounced in more terminally differentiated keratinocyte cultures, consistent with the ability of TCDD to activate AhR more effectively in differentiating keratinocytes (Swanson, 2004). During differentiation, keratinocytes acquire regulatory cofactors (e.g., calcium, nucleotides) in their cellular milieu essential for post-translational processing and catalytic activation of expressed TGM proteins; this occurs mainly in the outer epidermal layers (Gibson et al, 1996).…”
Section: Discussionmentioning
confidence: 59%
“…In this study, we also demonstrate a correlation be- tween the inhibition of PLD activation and of increased transglutaminase activity in response to TPA, suggesting a role for PLD in this process. It should be noted that transglutaminase activity is considered a marker of late keratinocyte differentiation, with enzymatic activity regulated at multiple levels, including transcriptionally, translationally, and post-translationally (Gibson et al, 1996). Therefore, an ability of the agents used in this study to inhibit TPAinduced transglutaminase activity suggests a more general effect on keratinocyte differentiation.…”
Section: Discussionmentioning
confidence: 85%